(untitled) (International Journal of Physiotherapy, 2020)
Background: Serious, major meniscal fractures are the most common knee injuries. In the management of meniscal tears, physical therapy has shown positive results, and additional medication is required to reduce the effects of meniscal tears. This study aimed to evaluate the feasibility of the mulligan squeeze procedure in combination with conventional pain relief therapy and to increase the range of movement and functional ability of meniscal tear patients. The study aims at reviving pain, increasing ROM and stability, and improving the quality of their lives. Methods: In this randomized controlled trial, 40 patients were chosen and randomly assigned to two groups, A and B, clinically diagnosed with a meniscal tear. The Numeric Pain Rating Scale (NPRS), the Patient-Specific Functional Scale (PSFS), and knee range of motion were reported to determine the pain level and functional capability of the patients. Results: During the 4th and 6th week, all classes showed a significant gap (P<0.05). At the end of the 6th week, the standard variance and the overall analysis team t-test values were higher than the control group. Conclusion: The two teams showed significant progress for NRPS, ROM, and PSFS, but the experimental group showed more significant improvement in all the parameters.